2019
DOI: 10.29359/bjhpa.11.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Association between gait speed and muscle mass and strength in postmenopausal women

Abstract: Background: Gait speed (GS) is the most popular tool used in clinical practice to diagnose functional performance.In order to maintain the independence of the elderly, it is useful to determine the association between gait speed and skeletal muscle mass, as well as the strength of the lower and upper extremities, which was the aim of this study. Material and methods:The study involved 95 women in the postmenopausal period. The skeletal muscle mass (SM) was determined using a bioelectric impedance method using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Cross-sectional design was used in eighteen studies, while cohort baseline data was used in four studies and RCT baseline data was used in one study. The studies were conducted on diverse regions, such as Japan (6 studies), 19 , 35 39 Brazil (5 studies), 40 44 Korea (3 studies), 45 47 United States (2 studies), 48 , 49 Indonesia (2 studies), 50 , 51 and one study in Germany, 52 Poland, 53 Norway, 54 Spain, 55 and Peru. 56 A total of 3580 (male = 1108, female = 2472) subjects were recorded from the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional design was used in eighteen studies, while cohort baseline data was used in four studies and RCT baseline data was used in one study. The studies were conducted on diverse regions, such as Japan (6 studies), 19 , 35 39 Brazil (5 studies), 40 44 Korea (3 studies), 45 47 United States (2 studies), 48 , 49 Indonesia (2 studies), 50 , 51 and one study in Germany, 52 Poland, 53 Norway, 54 Spain, 55 and Peru. 56 A total of 3580 (male = 1108, female = 2472) subjects were recorded from the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of the relationship between muscle mass and physical performance in older adults, 10 studies reported no significant association between these variables. 19,36,40,42,44,47,48,51,53 However, nine studies indicated a significant relationship between muscle mass and physical performance, with one…”
Section: Overall Outcomesmentioning
confidence: 99%
“…None of the studies discussed the normalization of speed to an individual’s leg length, although gait speed is directly affected by stride length. Other factors, such as lower extremity strength, may also contribute more to gait speed than thoracic kyphosis 60-63…”
Section: Discussionmentioning
confidence: 99%
“…Other factors, such as lower extremity strength, may also contribute more to gait speed than thoracic kyphosis. [60][61][62][63]…”
Section: Gait Speedmentioning
confidence: 99%
“…Of particular interest, a strong genetic correlation was observed between self-reported walking pace and handgrip strength, even after adjusting for body mass index (BMI), suggesting a shared genetic basis for these traits [ 4 ]. There is a close relationship between muscle strength, height and walking speed [ 3 , 5 , 6 , 7 ], and all of them are key intermediate phenotypes for sprinters [ 8 ]. Sprint speed is a product of step length and step rate; to sprint fast, first of all, one needs to be able to generate large strides, which requires muscle strength [ 9 ].…”
Section: Introductionmentioning
confidence: 99%